2021
DOI: 10.7759/cureus.13823
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic Manipulative Treatment to Optimize the Glymphatic Environment in Severe Traumatic Brain Injury Measured With Optic Nerve Sheath Diameter, Intracranial Pressure Monitoring, and Neurological Pupil Index

Abstract: Background Traumatic brain injury (TBI) has a complex pathophysiology that has historically been poorly understood. New evidence on the pathophysiology, molecular biology, and diagnostic studies involved in TBI have shed new light on optimizing rehabilitation and recovery. The goal of this study was to assess the effect of osteopathic manipulative treatment (OMT) on peripheral and central glial lymphatics in patients with severe TBI, brain edema, and elevated intracranial pressure (ICP) by measuring changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…This non-invasive method has been shown to correlate with elevated ICP in both instances of known pathology (i.e., trauma) and with IIH [ 43 , 44 ]. Although there are no current studies in the literature confirming a correlation between papilledema and NPi, quantitative pupillometry may be used as a surrogate to evaluate for papilledema [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…This non-invasive method has been shown to correlate with elevated ICP in both instances of known pathology (i.e., trauma) and with IIH [ 43 , 44 ]. Although there are no current studies in the literature confirming a correlation between papilledema and NPi, quantitative pupillometry may be used as a surrogate to evaluate for papilledema [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…Of course, muscles are not the only contributor to diagnosing an osteopathic lesion. This is apparent when performing the complex osteopathic examination of a patient with a traumatic spinal fracture, dislocation, subluxation, herniation, and traumatic brain injury (TBI) [ 9 ]. Although muscle is a large component, it is unknown whether the structure of the underlying anatomy can add much to the physicians’ diagnosis and whether that dis-ease of the structure can be directly restored.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the direct effects of OMT on ICP and ONSD. This study found significant improvements in ICP, ONSD, and NPI after OMT, which is hypothesized to be secondary to improved glymphatic functions [ 32 ]. These treatments optimized both lymphatic flow and drainage, which may decrease ICP by improving the flow of the glymphatic system.…”
Section: Reviewmentioning
confidence: 99%